Análisis e Interpretación a los Estados Financieros de la Compañía de Taxis “Sur Amigo Express” de la Ciudad de Loja en los Periodos 2014 - 2015 - Alvarez Abad, Doris Alexandra (2017)
The thesis entitled "ANALYSIS AND INTERPRETATION OF STATES FINANCIAL SERVICES OF THE TAXIS COMPANY "SUR AMIGO EXPRESS" OF THE CITY OF THE SHOP IN THE PERIOD 2014 - 2015 ", allows to fulfill the objectives proposed and that make reference to carry out a vertical, horizontal analysis and application of financial indexes, with the In order to determine the true economic situation of the company, in the years under study. The methodology applied for its execution consisted of gathering reliable and reliable information by the authorities of the organization, in order to restructure the financial statements and to apply the procedures of the financial analysis and determine their liquidity, indebtedness and profitability situation. In the evaluated years. After applying the practical part of the financial analysis, it is possible to construct the main conclusions reached, emphasizing that the company has economic solvency to face its obligations with third parties, in the same way, its structure reflects that it is liquid. As it has enough current assets to pay off debts with a term of less than one year.